2017
DOI: 10.14740/jem449w
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Consumption of Soy and Its Derivatives During Critical Periods of Development and in Adulthood and Endocrine-Metabolic Disorders

Abstract: The consumption of soybeans and their constituents, isolated soy protein and isoflavones, has been associated with positive effects on body weight, lipid profile and insulin, which has stimulated the production and consumption of foods derived from soy. However, these polyphenolic compounds (isoflavones) have similar structure to 17-β estradiol and may act as agonists or antagonists in estrogen receptors. Due to its estrogenic activity, the safety of its consumption during critical periods of development, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…This reinforces the idea that foods have different effects when consumed as a nutrient or bioactive component alone, especially during a critical period in life 22 . It is known that exposure to different factors in critical phases of life, such as lactation, can promote metabolic changes in the progeny, programming it for health or disease [12][13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reinforces the idea that foods have different effects when consumed as a nutrient or bioactive component alone, especially during a critical period in life 22 . It is known that exposure to different factors in critical phases of life, such as lactation, can promote metabolic changes in the progeny, programming it for health or disease [12][13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the Developmental Origins of Health and Disease theory, environmental conditions, nutrition, and/or hormones influence homeostatic regulation in the early stages of life and the development or protection against diseases throughout the stages of life [12][13][14][15] . Several studies have shown that nutrition during lactation can increase [16][17][18][19] or decrease 20,21 the risk of developing diseases in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Although the benefits of consuming soya products have been reported in many studies, consuming soya products containing phytoestrogens raises concerns (49) . Studies suggest that they may be associated with endocrine-metabolic dysfunctions in adult life (50) , and maternal consumption of soya protein isolate during lactation worsened the atherogenic indices of the offsprings in adulthood (51) .…”
Section: Limitations Of the Scoping Reviewmentioning
confidence: 99%
“…Programming at a critical stage of development can lead to changes in tissues and organs, which extend throughout life; it may also present a latency period and manifest only in adult life. More studies are emerging to explain the possible mechanisms related to metabolic programming [11,12].…”
Section: Introductionmentioning
confidence: 99%